Editorial - Cambridge OER 2012 - Anna Comas-Quinn; Alannah Fitzgerald; Ian Fairweather (Journal of Interactive Media in Education, 2012)
<!--[if gte mso 9]> <![endif]--> This second JIME special edition on Open Educational Resources draws on the success of the recent Cambridge 2012 Conference, which was jointly hosted by the Open Course Ware Consortium (OCWC) and the Support Centre for Open Resources in Education (SCORE), at the University of Cambridge in the United Kingdom. Key themes from the conference on innovation, impact and collaboration for advancing OpenCourseWare and Open Educational Resources globally are presented in the papers in this special issue. <!--[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Cambria","serif"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-ansi-language:EN-US; mso-fareast-language:EN-US;} --> <!--[endif] -->